Peri-dome choroidal deepening in highly myopic eyes with dome-shaped maculas - Ohno-Matsui, Kyoko; Jonas, Jost B. (American journal of ophthalmology, 2017)
Purpose: To determine characteristics of peri-dome choroidal deepening (PDCD) surrounding dome-shaped maculas (DSMs) in highly myopic eyes. Design: Observational case series. Methods: Applying swept-source optical coherence tomography, we examined the posterior pole of highly myopic eyes with DSMs. Results: The study included 91 highly myopic eyes (67 patients; mean age: 60.0 ± 15.1 years; mean axial length: 30.0 ± 7.4 mm) with a mean dome height of the DSM of 232 ± 132 μm. PDCDs were detected in 53 (58%) eyes. Subfoveal choroidal thickness was significantly thinner in eyes with vs without PDCDs (35 ± 29 μm vs 62 ± 48 μm; P = .016), while both groups did not vary significantly (all P ≥ .25) in age, axial length, and dome height. In contrast to peripapillary intrachoroidal cavitations (ICCs), PDCDs consisted of a widened choroid without large low-reflective suprachoroidal spaces. Unlike peripapillary ICCs or macular ICCs, PDCDs were not associated with caving of the overlying retina or backward bowing of the sclera. In the region of the PDCDs, the Bruch membrane (BM) was shorter than the inner scleral surface. Defects of the BM overlying the PDCDs were detected in 20 (38%) eyes. Conclusions: PDCDs were common findings in highly myopic eyes with DSMs. PDCDs may be associated with a dome-induced inward push of the BM at the top of the DSM, leading to a compression of the subfoveal choroid and, owing to an increased strain of the BM on the dome's slopes, to a relative detachment of BM in the peri-dome region.
Available online 11 September 2017
Gesehen am 04.07.2018